Planeación Financiera, Herramienta Clave Para La Empresa Servicios Integrales Sein Sas (2021)
The analysis carried out for the company Servicios Integrales Sein SAS is related to the creation of a strategic and financial planning on the horizontal property sector. A detailed interview was conducted to diagnose a problem and generate a solution to the problem with a clear and precise approach, although there are still things to improve, correct and apply. The company has great aspirations and expectations of growth and as an analyst of Servicios Integrales Sein SAS we want to promote and encourage the company to obtain good results, have greater credibility when working with the horizontal property providing a clear, specific, concrete and effective expectation, of course all this in order to grow financially and internally and consolidate a strategic process in relation to the consumer and personnel management. Therefore, this planning will help the company to have a greater vision in its work, having positive answers and results with high success rates such as its raison d'être, its objectives, mission, vision, schedule, organization of the administrative and accounting area. This approach will provide us with knowledge and skills at the time of executing a strategic and financial planning.